Portable Minapadi Model and Its Performance for Urban Farming - Tri Julianto, Baskoro; Setiawan, Budi Indra; Saptomo, Satyanto Krido; Liyantono (PERTETA, 2025)
The conversion of agricultural land to non-agricultural uses has threatened the food supply of urban areas. While there are many unused open spaces in the areas that would have the potential to produce certain foods that are regularly consumed. It is then necessary to introduce cultivation techniques that match the area’s conditions and operable by the people with no, or less experience in farming. This study aims to come up with a portable Minapadi (paddy and fish) culture deemed suitable for urban farming and identify its performance to produce rice as well as fish. The model was tested for one season (99 days) with the main parameters observed being water balances, rice and fish production and revenue. Applying automatic irrigation without using electricity, the irrigation water consumption was 738 mm with an efficiency of 54%. Land and water productivity were 3.62 tons/ha and 0.96 kg/m³, respectively. The fish survival rate was 85% with total production of 3.34 kg and feed efficiency of 2.74. This model earned IDR7,054.94/m³ for rice and IDR36,989.82/m³ for fish with total revenue of IDR44,044.76/m³. These results confirmed that this minapadi model has potential application to support the development of urban agriculture.